The metabolic and mitogenic properties of basal insulin analogues. (February 2013) - Tennagels, Norbert; Werner, Ulrich
<x xml:space="preserve">Abstract</x> Context: Retrospective, observational studies have reported an association between diabetes treatment with insulin and a higher incidence of cancer. Objective: Overview the literature for in vitro and in vivo studies of the metabolic and mitogenic properties of basal insulin analogues and assess the implications for clinical use. Methods: Relevant studies were identified through PubMed and congress abstract database searches; data on metabolic and mitogenic signalling in relation to insulin treatment of diabetes are included in this review. Results: The balance of evidence shows that although some analogues have demonstrated mitogenic potency in some in vitro studies in cancer cell lines, these findings do not translate to the in vivo setting in animals or to the clinical setting in humans. Conclusions: The current consensus is that there is no clinical or in vivo evidence to indicate that any commercially available insulin analogue has carcinogenic effects. Large-scale, prospective clinical and observational studies will further establish any potential link.